An experimental and numerical study on phase change material melting rate enhancement for a horizontal semi-circular shell and tube thermal energy storage system. (January 2022) - Kumar, Amit; Verma, Prashant; Varshney, L.
Highlights: Analysis on the effect of inner tube position of semi-circular LHTES unit on the melting performance of PCM Numerical comparison of semi-circular and circular shell configurations for fast melting rate of PCM. Simulation of the effect of LHTES shell geometries on the heat storage capacity of PCM Effect of Stefan number on the melting performance of PCM Abstract: In the present study, the melting characteristics of a lauric acid in a semi-circular and circular latent heat thermal energy storage unit have been studied. The low melting rate of phase change materials in the lower half of a circular heat storage unit can be enhanced by confining the phase change material in the upper region by configuring the outer shell of a conventional circular latent heat thermal energy storage unit into a semi-circular shape. The recent literature shows that no work has been carried out on the effect of the melting performance of phase change material in a semi-circular latent heat thermal energy storage unit hence an effort has been made to investigate the melting performance of phase change material experimentally and numerically for semi-circular latent heat thermal energy storage unit. The enhancement in the melting rate at three different inner tube position values from the bottom surface of outer semi-circular shell has been investigated and it is found that the enhancement is more when the inner tube is nearest to the bottom surface of the outer shell.The semi-circular heat storage unit is also compared with circular heat storage unit by considering the equal volume of phase change material in both the cases. The semi-circular latent heat thermal energy storage system shows enhancement in melting performance of phase change material as compared to circular latent heat thermal energy storage system. The semi-circular latent heat thermal energy storage system melts the phase change material completely in almost half time as compared to circular latent heat thermal energy storage system. It is found that the thermal energy stored in phase change material for semi-circular latent heat thermal energy storage system is 416.4 kJ which is 12.04 % more as compared to thermal energy stored of phase change material for circular latent heat thermal energy storage for the same time duration of 4800 sec. It is also found that the maximum thermal energy storage rate attained in semi-circular latent heat thermal energy storage system is 0.15 kW whereas in circular latent heat thermal energy storage system it is 0.13 kW which is 25 % higher as compared to that of circular latent heat thermal energy storage system.